2006
DOI: 10.1200/jco.2006.24.18_suppl.8587
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in newly-diagnosed brain tumor patients

Abstract: 8587 Background: A symptom cluster is 2 or more co-occurring symptoms. Patients with brain tumors experience disease and treatment-related symptoms that impact their health-related quality of life (QOL). Identifying symptom clusters will facilitate treatment and improve QOL outcomes. Methods: 66 patients were enrolled in a phase III, placebo-controlled, double-blind, prospective randomized clinical trial assessing the effect of prophylactic d-methylphenidate (d-MPH) on QOL in newly diagnosed brain tumor patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 0 publications
0
29
1
Order By: Relevance
“…In a study by Yeh et al (2008), difficulty concentrating or paying attention, insomnia, lack of energy, feeling drowsy, feelings of sadness, worrying, irritability and sweating formed one symptom cluster, while Ivanova et al (2005) reported that emotional stress and sadness formed a separate cluster in their analysis. Gleason et al (2007) identified a similar symptom cluster called psychological status which included sadness, depression and anxiety in their study on patients newly diagnosed with brain tumours, although again, this study was conducted on an adult sample. Chen and Lin (2007) also found a psychological symptom cluster using the M.D.…”
Section: Associations Between Cancer Treatment and Symptom Clustersmentioning
confidence: 88%
“…In a study by Yeh et al (2008), difficulty concentrating or paying attention, insomnia, lack of energy, feeling drowsy, feelings of sadness, worrying, irritability and sweating formed one symptom cluster, while Ivanova et al (2005) reported that emotional stress and sadness formed a separate cluster in their analysis. Gleason et al (2007) identified a similar symptom cluster called psychological status which included sadness, depression and anxiety in their study on patients newly diagnosed with brain tumours, although again, this study was conducted on an adult sample. Chen and Lin (2007) also found a psychological symptom cluster using the M.D.…”
Section: Associations Between Cancer Treatment and Symptom Clustersmentioning
confidence: 88%
“…In this approach, the same statistical technique is repeated at each time point. There are several techniques from which to choose, including exploratory factor analysis (EFA; Chen et al, 2011;Gleason et al, 2007;E. Kim et al, 2009;H.…”
Section: Resultsmentioning
confidence: 99%
“…Because some items exhibited flooring or ceiling effects and some cells were sparse, we dichotomized the responses (0, 'not at all', 'a little bit' and 'somewhat', and 1, 'quite a bit' and 'very much'). Although patients in the two studies completed their FACT brain subscale assessment at different time points following initiation of their study intervention with donepezil, d-MPH or the placebo (study A at the end of radiation, then 4, 8 and 12 weeks following onset of d-MPH or placebo, and study B at 6, 12, 24 and 30 weeks following onset of donepezil), the symptoms that were experienced by patients in both studies were similar (Gleason et al, 2007). Furthermore, we inspected the patterns of change in symptoms over time within each study and did not find detectable differences.…”
Section: Description Of the Datamentioning
confidence: 99%
“…As a result, 13 items from the FACT brain subscale were included in the final analysis. A factor analysis unambiguously separates the items into three domains (Gleason et al, 2007), which we labelled cognition problems (six items), emotional problems (four items) and physical and functional problems (three items). We provided a representative item for each domain: 'I am losing hope in the fight against my illness' (emotional domain), 'I have difficulty expressing my thoughts' (cognitive domain) and 'I have a lack of energy' (physical domain).…”
Section: Description Of the Datamentioning
confidence: 99%
See 1 more Smart Citation